Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island. Issue 11 (26th October 2018) - Sun, Sai-Jun; Zhang, Li-Peng; Zhang, Rong-Qing; Ding, Xing; Zhu, Hong-Li; Zhang, Zhao-Feng; Sun, Wei-Dong
ABSTRACT: Both Pacific and Neo-Tethys plates had major influences on the Cretaceous magmatisms in southeastern China. The subduction of the Neo-Tethys plate is, however, not well studied. This paper reports zircon U–Pb ages, Lu–Hf isotopes, whole-rock geochemistry, and Sr–Nd isotopes for the Qianjia intrusive rocks in Hainan Island, southeast China. LA-inductively coupled plasma mass spectrometry zircon U–Pb dating of granites and dark enclave monzonite in the area yield magmatic crystallization ages of ca. 100 Ma, which are consistent with other Late Cretaceous granites, e.g. Baocheng, Tunchang, and Yaliang. Both rocks show high-K calc-alkaline compositions and metaluminous to weakly peraluminous signatures belonging to I-type rocks. They are enriched in the alkalis, Rb, Th, U, K, and light rare earth elements, depleted in Nb, Ta, Ti, and P, and characterized by high Al2 O3 contents (14–15 wt%) and high Mg # values (50–53). Among them, some of granodiorites have geochemical affinities of adakitic rocks. Zircon ε Hf ( t ) values range from −5.97 to −1.18, with fairly constant whole-rock Sr–Nd isotopes ( I Sr = 0.7084–0.7086; ε Nd ( t ) = −4.97 to −4.29) similar with those of the Cretaceous mafic dikes (136–81 Ma) in Hainan Island, which are the result of partial melting of subduction-related sub-continental lithospheric mantle. Combined with Sr–Nd isotopes and negative Hf isotope, Qianjia intrusive rocks were likely derived from hybrid melts of underplated continental crust-derived with mantle-derived, then experienced varied degrees of fractional crystallization. According to the latest geophysical, sedimentological, and geochemical data, previous authors identified a Cretaceous E–W-trend subduction zone in the northern margin of the South China Sea. Combined with the southern margin magmatisms (110–80 Ma) and magmatisms of 120 Ma distributed east–west ward from the Philippines to the Vietnam, We preferred that the subduction of the E–W-trend Neo-Tethys plate was the main geodynamic mechanism which induced the Cretaceous large-scale magmatisms in the southern margin of South China Block.